1999
DOI: 10.1007/s004010051083
|View full text |Cite
|
Sign up to set email alerts
|

Microinfarction as a result of hypertension in a primate model of cerebrovascular disease

Abstract: Ten adult cynomolgus monkeys were studied as a non-human primate model of hypertensive cerebrovascular disease. Seven were made hypertensive by surgical coarctation of the aorta and three served as unoperated controls. After survival periods of 8-30 months, the brains were serially sectioned and surveyed for neuropathological changes. The most conspicuous change was minute areas of microinfarction in the white and gray matter. The lesions were of irregular shape with an average maximum diameter of less than 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…We postulate that other hypertensive related pathologies that are not visualized by MRI, e.g. microinfarcts [32] , may contribute to cGM atrophy.…”
Section: Discussionmentioning
confidence: 93%
“…We postulate that other hypertensive related pathologies that are not visualized by MRI, e.g. microinfarcts [32] , may contribute to cGM atrophy.…”
Section: Discussionmentioning
confidence: 93%
“…The mildly neuroprotective anaesthesic agent, pentobarbitone, was used in 12 reports on SHR-SP (Sadoshima et al, 1983;Tamaki et al, 1984;Werber and Heistad, 1984;Mayhan et al, 1987Mayhan et al, , 1988Baumbach et al, 1988Baumbach et al, , 1994Hajdu et al, 1991;Yang et al, 1991Yang et al, , 1993Chillon and Baumbach, 1999;Maguire et al, 2004) and in 4 other studies (Rosenberg et al, 1990;Toshima et al, 2000;Whitehead et al, 2005a, b). The primate aortic coarctation studies used ketamine anaesthesia (Kemper et al, 1999(Kemper et al, , 2001Moore et al, 2002), though this is unlikely to affect the data, given the prolonged pathogenesis of the lesions. Compliance with animal welfare regulations (domain no.…”
Section: Methodological Characteristics Of Included Studiesmentioning
confidence: 99%
“…This produced cerebrovascular lesions and some myocardial hypertrophy and retinopathy, but no obvious change in lifespan. Tiny infarcts were seen-discrete regions < 0.5 mm diameter-with loss of neurons and myelin (Kemper et al, 1999(Kemper et al, , 2001). These were most abundant in forebrain white matter (more rarely in periventricular white matter) and also scattered in cerebral cortex, hippocampus, striatum, midbrain, and cerebellum (Garcia et al, 1981;Kemper et al, 1999Kemper et al, , 2001.…”
Section: Hypertensive Modelsmentioning
confidence: 99%
“…A recent clinical study demonstrated that elderly individuals with silent brain infarcts were at greater risk for dementia and cognitive decline than elderly individuals without such lesions [53]. In addition to the subcortical cerebral vascular lesions visible on MRI, microinfarctions, which are usually not visible on MRI, may also be present, especially in subjects with hypertension [28]. Hypertension has been shown as a risk factor for late-life cognitive impairment [12,32].…”
Section: Introductionmentioning
confidence: 99%